2001
DOI: 10.1111/1467-8624.00262
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Discontinuity of Behavioral Inhibition and Exuberance: Psychophysiological and Behavioral Influences across the First Four Years of Life

Abstract: Four-month-old infants were screened (N = 433) for temperamental patterns thought to predict behavioral inhibition, including motor reactivity and the expression of negative affect. Those selected (N = 153) were assessed at multiple age points across the first 4 years of life for behavioral signs of inhibition as well as psychophysiological markers of frontal electroencephalogram (EEG) asymmetry. Four-month temperament was modestly predictive of behavioral inhibition over the first 2 years of life and of behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
967
5
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 804 publications
(1,018 citation statements)
references
References 59 publications
37
967
5
9
Order By: Relevance
“…These analyses of temperament and stress reactivity were abstracted from a larger study focused on understanding the impact of child care quality assessed in family child care homes on children's physiology and behavior. Consequently, all of the children in the study attended family child care for at least 30 hours per week, an experience that has been associated with discontinuity in inhibition during childhood (Fox et al, 2001). Likewise, most of the children were Caucasian and had parents with at least a high school education.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses of temperament and stress reactivity were abstracted from a larger study focused on understanding the impact of child care quality assessed in family child care homes on children's physiology and behavior. Consequently, all of the children in the study attended family child care for at least 30 hours per week, an experience that has been associated with discontinuity in inhibition during childhood (Fox et al, 2001). Likewise, most of the children were Caucasian and had parents with at least a high school education.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, multiple studies (Davidson et al 1990;Davidson 1998;Sutton and Davidson 1997) have found that individuals who exhibit higher relative left-hemisphere dominance are characterized as higher in approach motivation and positive affective style, and that this characteristic may be protective against stress in at-risk children (Lopez-Duran et al 2012). In contrast, individuals who exhibit higher relative right-hemisphere dominance are characterized by withdrawal, negative emotional style, and poorer outcomes (Fox et al 2001;Miskovic et al 2010;Mitchell and Pössel 2011;Smith and Bell 2010). Although most studies have found these differences to pertain mainly to asymmetry of frontal cortical activity, two studies also found similar results at more temporal/central cortical locations (Davidson et al 1990;Sutton and Davidson 1997).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%
“…The studies associated with frontal asymmetry, for instance, include child temperament (Fox, Henderson, Rubin, Calkins, & Schmidt, 2001), self‐report measures of affect and personality (Tomarken & Davidson, 1994), social anxiety (Schmidt, 1999), or social status (Tomarken, Dichter, Garber, & Simien, 2004). Two main models were adopted to describe subjective asymmetries in brain activity within the frontal areas, that is the dispositional model of affective style, which postulates that people possess a general tendency to respond predominantly with either an approach or a withdrawal behavior independently from the situational differences (Balconi & Mazza, 2010; Davidson, 1998); the valence model, which supposes that cortical differences between the two hemispheres are attributable to positive versus negative valence of emotional conditions (Everhart, Carpenter, Carmona, Ethridge, & Demaree, 2003; Russel, 2003; Silberman & Weingartner, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Because the pattern of frontal EEG asymmetry at rest was found to be stable across time (Schmidt, Cote, Santesso, & Milner, 2003; Tomarken, Davidson, Wheeler, & Kinney, 1992) and its appearance early in life is predictive of personality aspects (Fox et al., 2001), some have argued that this metric represents a “trait‐like” marker of dispositional affective style (Davidson, 1993, 2000). …”
Section: Introductionmentioning
confidence: 99%